The problems of the families of the handicapped with Down's syndrome - Meshaal, Afrah Sami; Al-Rubaie, Talib Abdul Salem (Al-Adab Journal, 2021)
The research deals with the problems of the families of the handicapped, with general syndrome, and the families of the handicapped in the city of Baghdad, in a special way, and knowledge of their problems in Iraqi society, indicating their family problems. And what suffers a handicapped in the family. From the rest of the family and social members, we need society for them, inferior and social stigma due to their disability and behavioral, including habits of the handicapped child. And psychological towards his disability and educational. During his training and teaching in private institutes, it was difficult to pronounce and the exits of letters, and we do not forget also the problems of marriage were between rejection and acceptance, for fear of the parents on them that the disabled would not bear the responsibilities of disability and towards the family to be formed, the legal position, Islam, the handicapped, and the role of social service. In the field of caring for the handicapped.